A raindrop initially at rest having a mass of 0 . 0 1 kg starts to fall towards the center of the earth under its gravitational force. During the fall, the water vapors near it start coalescing uniformly over it, thereby increasing its mass at a constant rate of 0 . 0 0 5 kg/s .
Find the velocity ( in m/s ) of the raindrop 4 seconds after it starts to fall, to two decimal places.
Details and Assumptions:
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Why does a force act in the opposite direction? I thought there was no resistance?
Log in to reply
A force always acts in the opposite direction when the mass of the object is increasing. You can see this yourself if when differentiating newtons 2nd law to obtain F = ma, we take mass as variable too. Then, there will be an extra term v(dm/dt); same as above. This will again become 0 when dm = 0(constant mass) and thus giving us our well known eqn F=ma back.
p f − p i = ∫ t i t f F ( t ) d t
Where:
g = 1 0 m / s 2
F ( t ) = m ( t ) g = 1 0 ( 0 . 0 1 + 0 . 0 0 5 t ) k g
t i = 0 , t f = 4 s
m f = 0 . 0 1 + 0 . 0 0 5 t f = 0 . 0 1 + 0 . 0 0 5 × 4 = 0 . 0 0 3 k g
p i = 0 (since initially the raindrop is at rest), p f = m f v = 0 . 0 3 v
Then,
0 . 0 3 v − 0 0 . 0 3 v 0 . 0 3 v v = ∫ 0 4 1 0 ( 0 . 0 1 + 0 . 0 0 5 t ) d t = 1 0 ( 0 . 0 1 t + 0 . 0 0 2 5 t 2 ) ∣ 0 4 = 0 . 8 = 2 6 . 6 7 m / s 2
Error in 6 t h line, it should be 0 . 0 3 k g
Problem Loading...
Note Loading...
Set Loading...
As the particle falls down with a non-constant mass a thrust force acts upwards opposite to the motion of magnitude F t = d t d m v .
Since we have d t d m = 5 × 1 0 − 3 , on integration it gives m ( t ) = ( 5 t + 1 0 ) × 1 0 − 3 .
Now we have the equation of motion of the particle as :
a ( t ) = g − m 1 d t d m v ( t ) v ′ ( t ) = g − 5 t + 1 0 5 v ( t ) v ′ ( t ) ( 5 t + 1 0 ) + 5 v ( t ) = g ( 5 t + 1 0 ) ( 5 t + 1 0 ) v ( t ) = ∫ 0 t g ( 5 t + 1 0 ) d t v ( t ) = t + 2 5 t ( t + 4 )
Putting t = 4 we get velocity as 3 8 0 ≈ 2 6 . 6 7